Accuracy of Cameriere method in chronological age estimation - Shahrzad Javadinejad; Mozhdeh Mehdizadeh; Reihaneh Torabi (مجله دانشکده دندانپزشکی اصفهان, 2012)
Introduction: Various dental age estimation methods have been used, based on tooth development. In Cameriere method the distance of the apices of seven left permanent mandibular teeth is measured. The aim of this study was to compare dental age means estimated by Cameriere method and the means of chronological age. Materials and Methods: In this cross-sectional descriptive study, 109 panoramic radiographs of 67 females and 42 males aged 5‒15 years were assessed. The variables included the number of teeth with full development and closed apices, the distance between the inner sides of open apices in immature teeth, and the tooth lengths. To accommodate the effect of magnification and x-ray angulation, the measurements were normalized by dividing them by tooth lengths. Finally, the normalized measurements of open apices, the sum of the normalized open apices, the number of teeth with closed apices, gender and chronological age were recorded using SPSS 18 for age estimation formula. Data were analyzed by Pearson’s correlation coefficient and independent t-test (α = 0.05). Results: Pearson’s correlation coefficient showed significant and inverse correlations between age and all the other variables. Differences between dental and chronological ages varied from -2.66 to 2.79 years. The median of chronological age was 10.67 and that of Cameriere age was 11.12 years. The difference between chronological age and estimated age was not significant (p value = 0.95). The differences between chronological and Cameriere ages were 0.73 in girls and 0.99 in boys. Estimated age was more accurate in girls (p value = 0.04). Conclusion: The present study indicated that Cameriere method was reliable for age estimation in our sample; also this method of age estimation was more accurate for girls than for boys. Key words: Age factor, Forensic dentistry, Panoramic radiograph, Tooth apex.